Trick or treat murder ebook - Meier, Leslie (Lucy Stone, 2013)
In this little Maine town, Halloween brings a homicide: "[A] charming setting and likable cast...enjoyable reading."— Publishers Weekly The locals in Tinker's Cove are busy planning haunted-house parties and ghostly galas, and Lucy Stone is whipping up orange-frosted cupcakes, recycling tutus for her daughters' costumes, helping her son with his pre-teen rebellion, and breast-feeding her brand-new baby. But amid the fun, something really scary is going on: An arsonist is loose, and when the latest fire claims the life of the owner of the town's oldest house, arson turns into murder. While the townsfolk work to transform a dilapidated mansion into a haunted house for the All-Ghouls festival, the hunt for the culprit heats up. Trick-or-treat turns deadly as digging in all the wrong places puts Lucy too close to a shocking discovery that could send all her best-laid plans up in smoke... "Lucy Stone is an endearing sleuth."—Dorothy Cannell